2007
DOI: 10.1111/j.1399-3054.2006.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

A Myb transcription factor (TaMyb1) from wheat roots is expressed during hypoxia: roles in response to the oxygen concentration in root environment and abiotic stresses

Abstract: Oxygen deficiency is one of the major stresses to plants under waterlogging. A low‐oxygen‐signaling pathway is the most important mechanism for adaptation and survival under anaerobic conditions. To find genes related to the oxygen concentration in root environment in common wheat roots, we investigated the transcriptional expression in vitro for low‐oxygen treatment. Dramatic increases in the transcripts of a TaMyb1 (Triticum aestivum Myb transcription factor 1) gene occurred under hypoxia. Presence of TaMyb1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 46 publications
0
58
1
2
Order By: Relevance
“…Seeds were germinated for 36 h at room temperature and transferred to a Magenta box (6.5 × 6.5 × 20 cm, Greenpia Technology Inc.) containing polypro mesh (polypropylene mesh opening 0.1 cm, Small Parts Inc.) as described by previous paper (Lee et al, 2007). The seedlings were grown in a Magenta box filled with 180 ml of a half strength of Hoagland's nutrient solution no.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds were germinated for 36 h at room temperature and transferred to a Magenta box (6.5 × 6.5 × 20 cm, Greenpia Technology Inc.) containing polypro mesh (polypropylene mesh opening 0.1 cm, Small Parts Inc.) as described by previous paper (Lee et al, 2007). The seedlings were grown in a Magenta box filled with 180 ml of a half strength of Hoagland's nutrient solution no.…”
Section: Methodsmentioning
confidence: 99%
“…Several of these TFs affect survival in low-oxygen or flooding stress (i.e. MYBs [Hoeren et al, 1998;Lee et al, 2007;Mattana et al, 2007], ERFs Xu et al, 2006;Hattori et al, 2009], and NAC [Christianson et al, 2009]). Despite conservation of some TF families between higher plants and Chlamydomonas (Supplemental Table S4), there was only limited induction of closely related TFs in the plant and algae species evaluated.…”
Section: Limited Conservation Of Regulatory Proteinsmentioning
confidence: 99%
“…High salinity affect plants in two main ways: high concentration of salts in the soil disturbs the capacity of roots to extract water and high concentration of salts within the plant itself can be toxic [47]. Some MYB proteins have effects on salt responses, such as TaMYB1, OsMYB3R-2, GmMYB76, GmMYB92, GmMYB177, and AtMYB41 [32,[48][49][50]. Furthermore, AhMYB6 and TaMYB33 also exhibit enhanced salinity tolerance in peanut and wheat, respectively [19].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis revealed that, the closest PgMYB1 homologs are tobacco NtMYB1 (AAB41101.1), potato StMYB4 (XP_006354484.1), tomato SlMYB4 (XP_004247733.1), carrot DcMYB1 (BAE54312.1), and peanut AhMYB6 (AHB59594.1) with 58%, 60%, 59%, 58%, and 51% similarity, respectively. Interestingly, the majority of R2R3-MYB proteins identical to PgMYB1 have been shown to be involved in response to various environmental stresses, and some of these genes are constitutively expressed in certain tissues, such as leaves and roots involved in plant defense [31,32]. Expression analysis has indicated that NtMYB1 and NtMYB2 proteins play a role in the extrusion of defensive compounds in the leaves [22,23].…”
Section: Homology Analysismentioning
confidence: 99%